(untitled) (Journal of Engineering, 2009)
This paper is aiming to develop a numerical procedure using the finite element method for the analysis of soil consolidation by taking into consideration the loading and unloading cycles with particular emphases on the pore pressure built up. The study is concerned with trapezoidal cyclic loading. The shear stresses that are developed in the subsoil due to cyclic loading cause shear strains and change in the mean normal stresses due to distortion of soil element. Biot’s consolidation theory that adopted in this study may be able to take these changes into consideration. The results indicated that the excess pore water pressure increases with load cycles and finally, a steady state conditions are reached. This may be attributed to the undrained cyclic shearing stresses to the origin initial cyclic shear stress ratio. Also it can be explained that when the load is applied very fast the collapse load approaches that undrained conditions, whereas when the load is applied very slowly the collapse load approaches that under drained conditions. When the elastoplastic model is considered the pore pressure are considerably larger than those predicted by the elastic consolidation analysis. This can be attributed to the plastic volume strain that have been taken into consideration in the elastoplastic model.